Behavioural responses to automatic enrolment in workplace pension schemes - Robertson, Lynne Margaret Maclean; Robertson-Rose, Lynne Margaret Maclean (The University of Edinburgh, 2016)
In October 2012, the United Kingdom adopted nation-wide automatic enrolment into workplace pension schemes. Automatic enrolment on the current scale is a major undertaking but it is also an untested policy and it is important that we understand how individuals are adapting to these radical changes in pension provision. There is currently a lack of research into the dynamic decision-making processes that lie behind some individuals’ deviation from workplace pension scheme default settings. This exploratory study investigates the importance of financial planning, social relations, and the role of the employer to default adherence and deviation. The embedded case study comprises qualitative interviews with 25 middle-income employees of a large UK utility company. Participants were selected on the basis of socio-economic similarity but had variable behavioural responses to the default settings of their workplace pension scheme. The study uncovered different motives underpinning individuals’ reaction to membership defaults, contribution defaults, and investment fund defaults. Continued membership following automatic enrolment was driven by social pressures. Subsequent to enrolment, individuals tried to achieve a balance between current expenditure and saving for retirement. Property ownership and mortgage debt redemption were prioritised over additional pension scheme investment. The life-stage of the individual influenced how they reacted to the contribution default settings - default adherence appeared to be linked to unsettled personal lives and career insecurity. Motives for increasing contributions were household formation, parental ageing, and relationship breakdown. Saving strategies were influenced by parental accumulation of retirement assets and parental financial literacy. Employer-matching contributions were implicated in participants’ willingness to increase pension contributions beyond the minimum default; investment in share option schemes was offered as justification for limiting contributions to the maximum match. Employer endorsement effects, driven by trust in the employer’s intentions, were strongly implicated in fund default adherence and in investment diversification strategies: participants pointed to the employer’s promotion of the pension scheme and employer-provided financial seminars. Advice from older colleagues was also cited as influential in directing retirement savings behaviour. The research concludes that the employment context is crucial to understanding how middle-income employees react to the default settings in their workplace pension scheme.
Keywords: pensions; automatic enrolment; defined contribution; workplace pension schemes; behaviour